1982
DOI: 10.1093/nar/10.15.4803
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the cap binding protein of influenza virus

Abstract: The presence of a cap binding protein in influenza virus PR8 has recently been demonstrated by photoaffinity labelling with the cap-analogue (gamma [3 2P]-[4-(benzoylphenyl)methylamido]-7-methylguanosine 5'-triphosphate). This paper describes the identification of the labelled protein using two-dimensional gel electrophoresis. The protein is shown to be PB2, the smaller of the two basic P proteins in the polymerase complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
86
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 16 publications
5
86
0
Order By: Relevance
“…For instance, in¯uenza virus mutants carrying mutations in the PB2 gene show defect in capped RNA cleavage (Ulmanen et al 1983). Uniformly radiolabelled cap RNA could be cross-linked to the PB2 protein Blaas et al 1982;Penn et al 1982). The recombinant baculovirus-expressed PB2 alone is able to bind the cap structure in an isolated state (Shi et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in¯uenza virus mutants carrying mutations in the PB2 gene show defect in capped RNA cleavage (Ulmanen et al 1983). Uniformly radiolabelled cap RNA could be cross-linked to the PB2 protein Blaas et al 1982;Penn et al 1982). The recombinant baculovirus-expressed PB2 alone is able to bind the cap structure in an isolated state (Shi et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It contains motifs typical of an RNA-dependent RNA polymerase (Poch et al, 1990) that are essential for its biological activity (Biswas & Nayak, 1994). The PB2 subunit has been shown to interact with cap 1 structures (Blaas et al, 1982 ;Ulmanen et al, 1981), and its possible involvement in the endonucleolytic cleavage of the host cellular mRNA precursors has been reported (Hagen et al, 1994 ;Licheng et al, 1995). The experiments carried out with ts virus mutants with defects in the PA gene have shown that, under these conditions, there is a defect in viral RNA replication but not in viral transcription (Mahy, 1983), although the mechanism for this is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, vRNP is translocated to the nucleus for transcription and replication of the influenza virus genome, which are both carried out by RdRp (4). IAV RNA transcription undergoes a unique cap-snatching process, in which PB2 first binds to the 5= cap of the host mRNA (5,6), PA subsequently cleaves the host mRNA to produce capped RNA fragments with lengths of 10 to 13 nucleotides (7), and PB1 finally elongates the viral mRNA by RNA polymerization using the viral negative-sense RNA as a template (8). Of note, production of the primer RNA requires PB1 binding to the 5= and 3= end sequences of vRNA (9).…”
mentioning
confidence: 99%